Palestras TED: um novo gênero do discurso? - Miranda, Alessandra Alves Pereira Braga de (2016)
Modern society attaches great importance to the act of speaking in public, not unlike the Ancient Greek, though with considerable change in the socio-historical context. Evidence of this phenomenon are the emergence of companies specialized in creating corporate presentations, the thriving market for speakers, and particularly the substantial number of prominent broadcast lectures accessible on the Internet. A significant example is the object of this research: the TED lectures, available on video, that have reached more than one billion views in 2012, bringing together professionals from different fields of study and different parts of the world. The purpose of this research is to understand the functioning of such lectures in contemporary times. What factors led to the widespread dissemination of TED talks? Are such talks giving rise to a new genre of discourse? If so, what traits characterize it? To answer these questions we examined videos of TED talks based on an enunciative-discursive perspective, as proposed by Maingueneau. From the theoretical and methodological point of view, we worked with the notion of enunciation scenes, included therein the concepts of encompassing scene, generic scene and scenography, and the relationship between medium and discourse. Three videos were selected for this analysis based on their visibility, representativeness and timeliness criteria. The results allow us to identify traits that indicate the emergence of a new genre of discourse, as well as foment a reflection on the possibility of thinking TED talks as a hipergenre. This research also enables us to infer a relationship between TED talks and other genres, including their development, with the necessary adjustments, in education